Literature Documentation of Basic Research on Immunological Effect by Acupuncture and/or Moxibustion Treatment - TOHYA, Kazuo; KURIBAYASHI, Koichi; TAHARA, Souhei; FUKAZAWA, Yohji; KASAHARA, Yuki; OKUDA, Manabu (Zen Nihon Shinkyu Gakkai zasshi (Journal of the Japan Society of Acupuncture and Moxibustion), 2006)
The immunological research committee for acupuncture and moxibustion, which was primarily organized in 2004, has investigated previous reports on basic research describing the immunological effect with acupuncture and/or moxibustion treatment. According to the on-line database, we firstly selected 724 reports by keyword searches, which were finally narrowed down to 52 reports on experimental animal tests and 42 reports on clinical tests (72 English articles and 22 Japanese articles) by careful sorting. Then, we analyzed information such as the condition of acupuncture and/or moxibustion stimulation, subject of the test, and immunological parameter for assessment in the 94 reports. The findings showed that the previous research was performed under inconsistent methods that were difficult to organize, and it is suggested that more comparable and reproducible experiments are required for the progression of this research area in the future.